1999
DOI: 10.3171/jns.1999.91.6.0928
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive evaluation of the malignant potential of intracranial meningiomas performed using proton magnetic resonance spectroscopy

Abstract: Proton MR spectroscopy is a useful diagnostic method for determining the proliferative or malignant potential of meningiomas according to the Cho/Cr ratio. A lactate and/or methylene signal suggests a high-grade tumor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(45 citation statements)
references
References 38 publications
5
36
1
3
Order By: Relevance
“…31 Several methods, including positron-emission tomography, perfusion MR imaging, and MR spectroscopy, have been proposed to study tumor grading and malignant progression in glial neoplasms. [32][33][34][35][36][37] Spectroscopic methods in particular may be useful in eliciting the metabolic correlates of genetic progression of gliomas or the malignant potential of meningiomas 38,39 during follow-up neuro-oncologic imaging. The role of decreasing ADC as a biomarker of worsening histologic grade has been less widely studied in intracranial neoplasms [40][41][42] (M.S.…”
Section: Discussionmentioning
confidence: 99%
“…31 Several methods, including positron-emission tomography, perfusion MR imaging, and MR spectroscopy, have been proposed to study tumor grading and malignant progression in glial neoplasms. [32][33][34][35][36][37] Spectroscopic methods in particular may be useful in eliciting the metabolic correlates of genetic progression of gliomas or the malignant potential of meningiomas 38,39 during follow-up neuro-oncologic imaging. The role of decreasing ADC as a biomarker of worsening histologic grade has been less widely studied in intracranial neoplasms [40][41][42] (M.S.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear density was found to correlate with Cho values [19, 35, 36]. Correlations with MIB-1 and Ki-67 were found in proliferative meningioma [37], and in cerebral tumours [4, 38, 39]. In vitro, Sabatier et al [40] showed a significant rise in Cho with tumour grade, and in vivo, there was a correlation between Cho and tumour grade [5, 11, 17, 20, 22,41,42,43,44].…”
Section: Discussionmentioning
confidence: 99%
“…They increase in the presence of necrosis, and are generally characteristic of high-grade tumours [12, 13, 19, 20, 48,65,66,67,68]. Some authors have tried to separate primary neoplasm and metastasis [17, 66], metastasis of different origins [69] and tumours and meningiomas [18, 37] using lipids. There is a great signal variability for the same tumour type [11, 16, 17, 28, 44, 62, 70, 71].…”
Section: Discussionmentioning
confidence: 99%
“…Alanine tends to be particularly elevated in tumours of meningeal origin (Florian et al, 1995) and is present at MRS-visible concentrations in a significant proportion of, but not all, meningiomas [12 out of 30, in a series reported by Shino et al (1999)]. An example is shown in Figure 9.9(d).…”
Section: Types Of Neoplasmmentioning
confidence: 99%